BIAYA LINGKUNGAN DAN DAMPAKNYA DALAM PENENTUAN HARGA JUAL: Studi Kasus di Galaxy Waterpark Yogyakarta - Ambarwati, Lilik; Lovnia Erawati, Gusmila (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
One of the importance of environmental accounting for companies is the allocation of environmental costs, in this case the environmental costs presented in financial reports can show the real costs used in maintaining and managing the company's environment. Therefore, the aim of this research is to determine the classification and recognition of environmental costs due to waste management costs at Galaxy Waterpark, as well as to see the impact of environmental cost recognition on selling price calculations. The analytical method used is descriptive qualitative. The data in this research was obtained through interviews, observation and documentation compared with the classification theory of the environmental costs and Basic Framework for Presenting Financial Reports in SAK as well as the way companies use selling price calculations. Based on the research results, it can be seen that Galaxy Waterpark classification of environmental costs is not in accordance with Hansen and Mowen's theory, and the recording of environmental costs does not follow the Basic Framework for Presenting Financial Reports in SAK. This is evident from the presentation of environmental costs recorded in one space, namely expenditure costs in the profit and loss report (normative model). Recognition uses a cash-based method and does not apply recognition from Basic Framework for Presenting Financial Reports in SAK. To calculate ticket selling prices, we use the margin pricing formula, which indirectly involves operational cost components, which include environmental costs. So environmental costs are also a consideration in determining the selling price.